Tinjauan Yuridis Terhadap Kebutuhan Pembaharuan Regulasi Hak Cipta Di Indonesia Dalam Menghadapi Perkembangan Karya Cipta Berbasis Artificial Intelligence (AI) - Anggarini, Ni Kadek Listya; Rama, Bagus Gede Ari; Antari, Putu Eva Ditayani; Putra, Komang Satria Wibawa (Consensus : Jurnal Ilmu Hukum, 2025)
The development of artificial intelligence (AI) technology has created new challenges in Indonesia's copyright law system. Artificial intelligence is now capable of producing works of art, writing, music, and other forms of expression that previously could only be produced by humans. However, Law No. 28 of 2014 on Copyright is still oriented towards the concept of human authorship, whereby only humans are recognized as creators and copyright holders. This situation creates a legal vacuum in determining the legal status of creative works produced in part or in whole by AI. Issues arise regarding the determination of the creator, ownership of economic and moral rights, and legal liability for copyright infringement involving AI systems.  This article uses a normative legal research method with a conceptual and legislative approach to analyze the extent to which Indonesia's copyright law system is able to accommodate developments in AI technology. The results of the study show that the current legal system is not yet able to provide adequate protection for AI-based works due to the lack of clear criteria regarding the level of human involvement required to obtain copyright protection. Therefore, regulatory updates are needed in the form of amendments to Law Number 28 of 2014 or the issuance of implementing regulations that regulate the limits of human roles, transparency in the use of AI training data, and legal protection mechanisms for works involving algorithms. These updates are important to ensure legal certainty, protect the rights of human creators, and encourage technological innovation and the national creative economy in the digital era